Sequence dependence of Pd(II)-mediated base pairing by palladacyclic nucleobase surrogates - Hande Madhuri; Maity Sajal; Lönnberg Tuomas (Elsevier Inc., 2022)
A C-nucleoside derivative of phenylpyridine or the respective palladacycle was incorporated at either 3′- or 5′-terminus of a short oligodeoxynucleotide. Hybridization properties of these modified oligonucleotides were studied in a fluorescence-based competition assay in addition to conventional UV melting temperature analysis and compared with those of a previously prepared analogue featuring the modified nucleoside in the middle of the sequence. With the unpalladated phenylpyridine oligonucleotides, UV melting temperature qualitatively correlated with the ability to displace a strand from a double helix in the competition assay, decreasing in the order 5′ > 3′ > middle. Corresponding results on the palladacyclic oligonucleotides were more difficult to interpret but both UV melting and competition experiments revealed a decrease in the duplex stability upon palladation in most cases. On the other hand, dependence of the UV melting temperature on the identity of the canonical nucleobase opposite to the modified nucleobase analogue was much more pronounced with the palladacyclic duplexes than with their unpalladated counterparts. Furthermore, UV melting profiles of the palladacyclic duplexes featured an additional transition at a temperature exceeding the melting temperature of the unmodified part of the duplex. Taken together, these results lend support to the idea of
Pd(II)-mediated base pairs that are highly stable but incompatible with the geometry of a double helix.
Graphical abstract
Hybridization properties of oligonucleotides incorporating a phenylpyridine C-nucleoside or its palladacyclic derivative were studied by a fluorescence-based competition assay in addition to conventional melting temperature measurements. Position of the modification had a major impact on duplex stability even when the canonical base opposite to the modified base remained unchanged.
.